1998
DOI: 10.1038/bjc.1998.267
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in 144 brain tumours

Abstract: Summary Unlimited proliferation in immortalized cells is believed to be highly dependent on the activity of telomerase, a ribonucleoprotein that synthesizes telomeric repeats onto chromosome ends. Using a polymerase chain reaction-based telomeric repeat amplification protocol (TRAP) assay, we analysed telomerase activity in 99 benign and 45 malignant brain tumours. The TRAP assay results were quantitated by normalizing the telomerase activity of each specimen to that of human glioma cell line T98G to obtain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
4
24
1
Order By: Relevance
“…Furthermore, the percentage of TERT promoter mutations in oligoastrocytomas, gliomas with a mixed origin, is intermediate between that of oligodendrogliomas and astrocytomas [58]. These findings fit with the reported data on telomerase activity in gliomas which is considerably higher in GBM (50-89 %) and oligodendrogliomas (75-100 %), than in astrocytomas (0-45 %) [49,67,106]. The low frequency of TERT promoter mutations and telomerase activity in grades II and III astrocytomas can be explained by the high prevalence of ATRX mutations, one of the most frequent mutations in this type of glioma [56].…”
Section: Telomerase Promoter Mutations In Bladder Carcinomassupporting
confidence: 87%
“…Furthermore, the percentage of TERT promoter mutations in oligoastrocytomas, gliomas with a mixed origin, is intermediate between that of oligodendrogliomas and astrocytomas [58]. These findings fit with the reported data on telomerase activity in gliomas which is considerably higher in GBM (50-89 %) and oligodendrogliomas (75-100 %), than in astrocytomas (0-45 %) [49,67,106]. The low frequency of TERT promoter mutations and telomerase activity in grades II and III astrocytomas can be explained by the high prevalence of ATRX mutations, one of the most frequent mutations in this type of glioma [56].…”
Section: Telomerase Promoter Mutations In Bladder Carcinomassupporting
confidence: 87%
“…Telomerase activity, which is generally undetectable in normal somatic cells, is expressed in approximately 90% of tumors (Kim et al, 1994;Broccoli et al, 1995;Hiyama et al, 1995). In malignant gliomas, telomerase activity is very often detected (Table 1) (Langford et al, 1995;DeMasters et al, 1997;Sallinen et al, 1997;Sano et al, 1998;Kleinschmidt-DeMasters et al, 1998;Chong et al, 1998;Hiraga et al, 1998;Le et al, 1998;Weil et al, 1999;Carroll et al, 1999;Falchetti et al, 1999;Huang et al, 1999;Kleinschmidt-DeMasters et al, 2000;Harada et al, 2000). In Grade I or II of gliomas, telomerase activity is detected in 0% or 0 to 33%, respectively.…”
Section: Telomerase In Malignant Gliomasmentioning
confidence: 99%
“…Almost 80-90 % of human cancers display telomerase activity. Several studies showed that more than 50 % of gliomas display telomerase activity and its detection rates increases with the grades of malignancy (Langford et al 1995;Nakatani et al 1997;Sano et al 1998;Tchirkov et al 2003). Much attention has been given to telomerase, however, telomerase independent mechanism like alternative lengthening of telomeres (ALT) can also maintain telomere lengths in cancer cells by homologous recombination between telomere sister chromatids (Cesare and Reddel 2010).…”
Section: Introductionmentioning
confidence: 99%